2001
DOI: 10.1126/science.1059495
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Transcription: An RNA Polymerase II Elongation Complex at 3.3 Å Resolution

Abstract: The crystal structure of RNA polymerase II in the act of transcription was determined at 3.3 Å resolution. Duplex DNA is seen entering the main cleft of the enzyme and unwinding before the active site. Nine base pairs of DNA-RNA hybrid extend from the active center at nearly right angles to the entering DNA, with the 3′ end of the RNA in the nucleotide addition site. The 3′ end is positioned above a pore, through which nucleotides may enter and through which RNA may be extruded during back-tracking. The 5′-mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
960
7
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 850 publications
(1,016 citation statements)
references
References 41 publications
44
960
7
5
Order By: Relevance
“…In contrast, the downstream DNA in the Pol I PIC is in a similar position to previous DNA‐bound structures of Pol I (Neyer et al , 2016; Tafur et al , 2016) and Pol II (Gnatt et al , 2001; Fig 2C) demonstrating that downstream DNA is retained inside the DNA binding cleft during the transition from initiation to elongation. These findings also agree with previous structures showing that Pol I and Pol II can position downstream DNA correctly in the absence of transcription factors and RNA (Cheung et al , 2011; Tafur et al , 2016).…”
Section: Resultssupporting
confidence: 78%
“…In contrast, the downstream DNA in the Pol I PIC is in a similar position to previous DNA‐bound structures of Pol I (Neyer et al , 2016; Tafur et al , 2016) and Pol II (Gnatt et al , 2001; Fig 2C) demonstrating that downstream DNA is retained inside the DNA binding cleft during the transition from initiation to elongation. These findings also agree with previous structures showing that Pol I and Pol II can position downstream DNA correctly in the absence of transcription factors and RNA (Cheung et al , 2011; Tafur et al , 2016).…”
Section: Resultssupporting
confidence: 78%
“…Template bases in positions +1/+2 are twisted against each other by about 901 in structures of the undamaged elongation complex 9,13 , but such twisting is impossible for nucleotides that are covalently linked in dinucleotide lesions, giving rise to a translocation barrier 8 . To determine whether translocation of the cisplatin lesion is indeed impaired, we crystallized complex B, which was designed to contain the dimer at positions +1/+2 (scaffold B, Fig.…”
Section: Impaired Entry Of Lesions Into the Active Sitementioning
confidence: 99%
“…This structure revealed that the DNA-RNA hybrid is present in the enzyme cleft, and provided important insights into elongation [9]. Experimental limitations of this system have been overcome in recent studies by reconstituting ECs with synthetic nucleic acids.…”
Section: Rna Polymerase II Elongation Complex Structuresmentioning
confidence: 97%
“…Although an atomic model of the 10-subunit core of Pol II was available [8,9], only backbone models of complete 12-subunit Pol II, which comprises the core and the Rpb4/7 subcomplex, had been reported [10,11]. A new structure of free Pol II subcomplex Rpb4/7 has now enabled refinement of an atomic model of complete Pol II [12 ].…”
Section: Introductionmentioning
confidence: 99%